Ultrashort pulse thulium-doped fiber laser with molybdenum trioxide on tapered fiber - Ahmed, M. H. M.; Mohd Yusoff, N.; Zainol Abidin, N. H. H.; Lee, H. K.; Alresheedi, M. T.; Abas, A. F.; Goh, C. S.; Mahdi, M.A. (Elsevier, 2022)
This paper demonstrates ultrashort pulse generation using molybdenum trioxide (MoO3) saturable absorber (SA) integrated into a thulium-doped fiber laser. The average particle size of the MoO3 material was 9.54 µm. The MoO3/polydimethylsiloxane composite was prepared and spin-coated on a tapered fiber to fabricate the SA device. It had a modulation depth of 2.89% and demonstrated a high damage threshold, extending beyond 19.34 GW/cm2. From the evanescent light-matter interaction, stable self-starting mode-locked soliton pulses of 1.22 ps duration at 1941.4 nm central wavelength were obtained. The pulse repetition rate was 10.84 MHz with 3.3 nm spectral bandwidth. At 1.15 W pump power, the soliton pulse energy was 0.68 nJ corresponding to a peak power of 492 W. The work exhibited comparable pulse performances in the 2 µm wavelength range while utilizing simple SA fabrication procedures of micro-sized MoO3 materials.